ICE mediation/conciliation procedure (ICE, 2012)
The ICE Mediation/Conciliation Procedure can be used with almost all forms of contract, is applicable throughout the construction industry, and allows for prompt resolution regardless of the size or nature of the dispute.
Keywords: Mediation and conciliation, Industrial -- Great Britain.; Construction industry -- Great Britain.; elektronické knihy; electronic books